The Self-Concept of Ale Rasa Beta Rasa in the Orang Basudara Community in Ambon (Studies on the Community of Passo and Batumerah Country) - Matakena, Fransina; Watloly, Aholiab; Agustang, Andi; Adam, Arlin; Alim, Andi (International Journal of Criminology and Sociology, 2022)
Ambon city is known as a city with diverse cultural wisdom. Local wisdom has moral values that are always taught from generation to generation by the Ambonese community orally or in writing. In Maluku culture, there are strong territorial ties to Genolosis in resolving conflicts or social structures built by ancestors to bridge differences in Maluku. One of the efforts to care for the Maluku community’s social order is to revive the concept of ale rasa beta rasa in the orang Basudara community. The idea of "ale rasa beta rasa" is a manifestation of a cognitive effort by the Moluccans to create a harmonious, safe, and peaceful brotherly relationship. This research aims to analyze the implementation self-concept of ale rasa beta rasa in the orang Basudara community. This research uses a descriptive qualitative method—research location in Ambon City in the Study of Passo and Batumerah Community Communities, Maluku Province. Data collection was carried out by observation, in-depth interviews, and or focused group discussion (FGD). The research results show that Ale (you) taste beta (I) feel a concept that sociologically contains deep meaning for the Ambonese community. There are philosophical values in the expression Ale Rasa Beta Rasa . The value content is not only material for thought, but in the form of daily praxis to respect, feel, and carry out customary sacred duties. The values of Ale Rasa Beta Rasa function entirely and totally in carrying out the development of the life of the Basudara in Maluku. These values can operate functionally in building harmony, peace, progress, and the welfare of the Maluku nation’s children. Ale and Beta have not only a communicative textual function but also a taste function as an expression of the heart and spirit of brotherhood. Ale rasa beta rasa becomes a means of reconciliation for conflicts between siblings. There is a content of philosophical values in the expression Ale Rasa Beta Rasa. it’s just that the valuable content is still thoughtful and is manifested in everyday behavior to share, feel, and carry out sacred traditional events. There is a relationship between the values of Ale Rasa Beta Rasa and the self-concept and life context of the Basudara in Maluku, especially in the Pela relationship between Negeri Batumerah and Passo.